DEVELOPMENT OF STRAIGHT LINE EQUATION MODULE BASED ON GUIDED INQUIRY LEARNING TO IMPROVE THE MATHEMATICAL CONNECTION ABILITY OF MIDDLE SCHOOL STUDENTS - Almunir Sihotang; Muhammad Subianto; Zainal Abidin (EduMa: Mathematics education learning and teaching, 2019)
Seeing students' mathematical connection ability is low, indicating that students' ability to study mathematics is also low. The media that fits this condition is the learning module. The research problem formulation is whether the development of guided inquiry based straight line equation learning can improve the mathematical connection ability of class VIII students?. The purpose of this research is to know module learning development equation-based guided inquiry straight line can improve the ability of class VIII student of mathematical connections. This research is through the Research and Development (R and D) research process. The subject of this research is the State Middle School students 3 Unggul Ingin Jaya as many as 20 students. The analysis in this study uses a questionnaire for students, the feasibility of a learning module that is an assessment by an expert (validator) using a questionnaire validity of material experts, student learning outcomes, student responses to the learning module. The results of the validator's assessment state an average of 3.45 in the valid category, while the average value of 3,25 in the category is quite effective. The average N-gain value of the experimental class is 0,36 compared to the N-gain average of the control class 0.33. The conclusions in this study are the development of a module of straight line equations with an inquiry approach can improve the mathematical connection ability of class VIII students of Middle School. Keywords: Module development equation of a straight line, connection matematics, Inquiry